Reconciling Between Optical and Biological Determinants of the Euphotic Zone Depth. Issue 5 (26th April 2021) - Wu, Jinghui; Lee, Zhongping; Xie, Yuyuan; Goes, Joaquim; Shang, Shaoling; Marra, John F.; Lin, Gong; Yang, Lei; Huang, Bangqin
Abstract: The conventional use of optically determined 1% of surface photosynthetically available radiation (PAR) depth ( Z 1% PAR, λ = 400–700 nm) as a metric for the euphotic zone depth ( Z eu ) has been a matter of debate for several decades because of frequent inconsistencies with the base of euphotic zone determined biologically, that is, the compensation depth ( Z c ). In this study, we attempt to reconcile between optical and biological determinants of the euphotic zone through the use of a large data set of coincidental profiles of downwelling irradiance and primary production. These measurements cover open ocean waters in the tropics, subtropics, temperate regions, and from two time‐series stations, the Hawaii Ocean Time‐series (HOT) and the Bermuda Atlantic Time‐series Study (BATS). We report that, at least for these measurements, Z 1% PAR is too shallow (by 14.1%) compared to Z c, while Z 0.1% PAR is too deep (by 32.7%). Further, the irradiance at Z c (i.e., the compensation irradiance, I c ) varies by a factor of more than five, but its ratio to surface irradiance is relatively stable. In general, I c corresponds to 0.48 ± 0.23% of surface PAR, or 0.87 ± 0.40% of surface usable solar radiation (USR, for λ = 400–560 nm), or 1.50 ± 0.67% of surface downwelling irradiance at 490 nm. These results suggest that Z 0.5% PAR, or Z 0.9% USR, or Z 1.5% 490 could be promising alternatives to bridge the optical and biological determinants of the euphotic zone depths for waters in the open ocean at low to middle latitudes. Plain Language Summary: Euphotic zone depth ( Z eu ) is an important and classical concept in biological oceanography, which serves as a useful measure of the layer that has meaningful photosynthesis or primary production (PP). Due to practical difficulties in assessing Z eu through measurements of PP, it has been widely done through the measurement of light intensity under the assumption that the depth of 1% PAR(0) is this Z eu . However, the use of 1% PAR(0) for estimating Z eu continues to be a matter of debate as this depth generally doesn't represent the biological Z eu (or compensation depth, Z c ). In this study, a large data set (234 points) has been analyzed, consisting of concurrent profiles of PP and light intensity from different parts of the global oceans and different water types, excluding high‐latitude regions. The results indicate that Z c matches well with the depth 0.5% of PAR(0) (Z0.5% PAR ), or the depth of 0.9% surface usable solar radiation (USR, λ = 400–560 nm) (Z0.9% USR ), or the depth of 1.5% of surface downwelling irradiance at 490 nm (Z1.5% 490 ). These results suggest that Z0.5% PAR, or Z0.9% USR, or Z1.5% 490 can be a promising approach to bridge optically and biologically derived Z eu at least for low‐to mid‐latitude waters. Key Points: The "euphotic zone" depth based on 1% or 0.1% surface photosynthetically available radiation (PAR) is not an accurate measure of the biological euphotic zone determined on the basis of photosynthetic rate measurements The compensation irradiance varies significantly and thus is not an operationally useful metric to define the base of the euphotic zone For low‐to mid‐latitude waters, depths of 0.5% of surface PAR, or 0.9% of surface usable solar radiation, or 1.5% of surface downwelling irradiance at 490 nm related better with the euphotic zone depth determined biologically